Incentivising and regulating multi-actor partnerships and private-sector engagement in development cooperation - Dorothea Wehrmann (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The inclusion of actors from the private sector is a central challenge for multi-actor partnerships (MAPs) and multi-stakeholder platforms in development cooperation. On the one side, the heterogeneity of approaches that shape development cooperation and rather abstract, long-term agendas (such as the 2030 Agenda for Sustainable Development) make it difficult to incentivise the engagement of private-sector actors that typically prefer concrete and short-term activities with predictable outcomes. On the other side, the effectiveness of past development initiatives with actors from the private sector has often proven to be limited. In order to identify strategies to meet this challenge, this discussion paper investigates the case of the Global Partnership for Effective Development Co-operation (GPEDC), a multi-actor partnership and platform striving for better inclusion of private-sector actors in development cooperation. More generally, the paper contributes to the debates on how multi-stakeholder networks and platforms can support the implementation of the Sustainable Development Goals by incentivising and regulating the collaboration of private-sector actors in MAPs. In addition, it also provides insights on the particularities of MAPs with private-sector actors in formats exemplifying so-called South-South cooperation. The latter have been widely neglected in the literature on networks and platforms so far but are important to consider, not least because of the growing significance of partners and alternative concepts from the “Global South” and the structural dynamics and changes they enhance in the field of development cooperation. In this regard, and under consideration of different conceptual perspectives, the paper examines how multi-stakeholder networks and platforms in general – and the GPEDC in particular – can provide a supporting structure that encourages the inclusion of private-sector actors and the effectiveness of sustainable development initiatives. To achieve both – to enhance the engagement of private-sector actors and the effectiveness of MAPs in development cooperation – this paper concludes that initiatives such as the GPEDC need to: strengthen the institutional oversight that they provide, support the formulation of explicit and case-specific incentivising- and regulating-strategies, give more weight to context-specific particularities of cooperation that apply, for example, in South-South cooperation.
Keywords: 330; Agenda 2030; Governance